Judicial review and the future of UK development assistance: On the Application of O v Secretary of State for International Development (2014). (29th June 2018) - Harrington, John; Manji, Ambreena
Abstract: In this paper we explore a case for judicial review brought against the Secretary of State for International Development by an Ethiopian national, Mr O. The claimant alleged that the Department for International Development (DfID) had failed adequately to assess evidence of human rights violations in Ethiopia to which funds provided by DfID had contributed. Warby J ruled that the claim merited a full hearing. DfID is unaccustomed to judicial review: the O case is the first time since the 1995 Pergau Dam case that UK development aid has been reviewed by the courts. We study Warby J's judgment and its implications for accountabiity for aid decisions. We argue that both the wider context for aid and the legal framework governing development assistance have changed significantly in the 20 or so years since Pergau . In particular, we show that despite the UK's new legal commitment, made in 2015, to spend 0.7% of gross national income (GNI) on official development assistance, the existing mechanisms for scrutinising aid decisions are inadequate. We argue that there is an accountability gap in relation to the UK's now considerable development spending and explore the role of judicial review in this context.